Valorization of raw and treated iron ore tailings in cement based materials: Insights on physicomechanical, microstructural, and environmental properties - Omur, Tarik; Akgun, Ali Eren; Ozkan, Aysegul Bilen; Kabay, Nihat (ELSEVIER SCI LTD, 2026)
The massive production of iron ore tailings (IOT) presents considerable environmental and storage issues, yet the potential valorization ways of raw or treated IOT in cementitious systems remains underutilized. This study investigates the feasibility of employing raw (R-IOT) and thermally treated IOT (T-IOT) as both binder and natural sand replacements, with emphasis on revealing how thermal activation modifies their reactivity and sustainability performance. The optimum calcination temperature of IOT was determined via mechanical tests and mineralogical analysis. Rheology, setting time, pH evolution, long term compressive strength, and microstructural properties of IOT-cement mixtures were compherensively studied. The mortars incorporating IOT as sand replacement were further evaluated through capillary water sorptivity, chloride migration tests, and life cycle assessment (LCA). Pozzolanic activity test results indicated that thermal activation at 800 degrees C significantly ameliorated the pozzolanic activity of IOT, increasing compressive strength from 0.4 MPa to 4.9 MPa and boosting strength activity indices to 97.7% at 7 days. The cement replacement levels of 10-20% improved or maintained the mechanical strength relative to the reference. While higher dosages exhibited diminished earlyage strength, a substantial recovery was achieved by 90 days due to pozzolanic C-(A)-S-H formation. As a filler, both R-IOT and T-IOT enhanced long-term mechanical performance, with T-IOT achieving up to 43% higher 90day strength than the reference mortar. The physical and durability properties of T-IOT containing mortars remained comparable or improved compared to reference mortar. LCA revealed notable CO2 reductions up to 28% and energy demand savings up to 9.5% when IOT replaced cement. Overall, T-IOT demonstrates strong potential as a sustainable and high performance material in mortar, providing both environmental benefits and improved performance.
Keywords: Iron ore tailing; Pozzolanic activity; Thermal treatment; Filler; Life cycle assessment; X-RAY; TEMPERATURE; STRENGTH; WASTE; Construction & Building Technology; Engineering; Materials Science